COMPUTATION OF WAVE CHARACTERISTICS IN THE OFFSHORE REGION USING NUMERICAL MODEL WAM - Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2006)
COMPUTATION OF WAVE CHARACTERISTICS IN THE OFFSHORE REGION USING NUMERICAL MODEL WAM